2017
DOI: 10.3892/or.2017.5466
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages favor C26 murine colon carcinoma cell proliferation in an oxidative stress-dependent manner

Abstract: The role of tumor-associated macrophages (TAMs) in the development of colon carcinoma is still controversial. Therefore, the present study aimed to investigate the TAM‑driven processes that may affect colon cancer cell proliferation. To achieve this purpose, murine macrophages were co-cultured with C26 murine colon carcinoma cells at a cell density ratio that approximates physiological conditions for colon carcinoma development in vivo. In this respect, the effects of TAM-mediated angiogenesis, inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…One study confirmed that TAMs-driven oxidative stress, the pro-oxidant enzyme NADPH oxidase in macrophages, was significantly reduced. TAMs contributed to the development of colon carcinoma in an oxidative stress-dependent manner that potentiated the redox status and the angiogenic capacity of the tumor microenvironment [51]. It was found that after co-culturing TAMs with SW480 colon cancer cells, MMP-9 expression was increased, and the epithelial-mesenchymal transition proteins E-cadherin, β-catenin, vimentin, and snail were induced in SW480 cells.…”
Section: Tams-mediated Effects On the Tumor Microenvironment And Crc mentioning
confidence: 99%
“…One study confirmed that TAMs-driven oxidative stress, the pro-oxidant enzyme NADPH oxidase in macrophages, was significantly reduced. TAMs contributed to the development of colon carcinoma in an oxidative stress-dependent manner that potentiated the redox status and the angiogenic capacity of the tumor microenvironment [51]. It was found that after co-culturing TAMs with SW480 colon cancer cells, MMP-9 expression was increased, and the epithelial-mesenchymal transition proteins E-cadherin, β-catenin, vimentin, and snail were induced in SW480 cells.…”
Section: Tams-mediated Effects On the Tumor Microenvironment And Crc mentioning
confidence: 99%
“…Tumor tissues from each experimental group were lysed as previously described, and the protein concentration was measured using the biuret method . The production of the active form of nuclear factor [NF]‐κB (2 µg total protein) (polyclonal rabbit IgG anti‐mouse pNF‐kB‐p65; Santa Cruz Biotechnology), Bcl‐2 (40 µg total protein) (monoclonal anti‐rabbit Bcl‐2; Cell Signaling Technology), and Bax (25 µg total protein) (rabbit polyclonal IgG anti‐Bcl‐2‐associated X protein; Cell Signaling Technology) were determined by western blot analysis, along with β‐actin (rabbit polyclonal IgG anti‐mouse β‐actin; Sigma‐Aldrich) as the loading control, as described previously . The secondary Ab used was goat anti‐rabbit IgG‐HRP‐conjugated (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the effects of the combined therapy on the production levels of angiogenic/inflammatory proteins in tumor tissue, we undertook screening for 24 proteins involved in angiogenesis using the RayBio Mouse Angiogenic Cytokine Antibody Array kit (RayBiotech) as described previously . The production of each angiogenic/inflammatory protein in tumor tissue lysates was determined in duplicate, and represented as mean ± SD of 2 independent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations